2021
DOI: 10.1021/acs.langmuir.1c02020
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Steric and Molecular Bonding Effects Contributing to the Stability of Neutrally Charged Nanoemulsions

Abstract: In cosmetic, pharmaceutical, and food applications, many active ingredients have limited bioavailability in an aqueous environment, and in that context, nanoemulsions provide a mechanism for encapsulation, protection, and transport. These dispersed oil droplets are on the order of 100s of nanometers in diameter and owe their long-term stability to emulsifiers that are commonly charged. More recently, applications have been utilizing nonionic species as stabilizing agents due to their enhanced biosafety. DLVO (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 58 publications
3
9
0
Order By: Relevance
“…This trend suggests that particles contain multiple crystallite domains. In all solvents, the nanoZIF-8 particles exhibit large and stable zeta potentials, as consistent with DLVO theory that colloids are stabilized by charged surface layers that repel neighboring particles and prevent aggregation. Although ZIF-8 particles have been reported to degrade gradually in water, these studies also suggested a strong concentration dependence where more dilute solution degraded faster, whereas the saturated solutions studied were prepared at far higher concentrations. Furthermore, these nanoZIF-8 methanolic suspensions display visual stability for at least one-month storage, requiring only gentle sonication (∼10 min.)…”
Section: Resultssupporting
confidence: 76%
“…This trend suggests that particles contain multiple crystallite domains. In all solvents, the nanoZIF-8 particles exhibit large and stable zeta potentials, as consistent with DLVO theory that colloids are stabilized by charged surface layers that repel neighboring particles and prevent aggregation. Although ZIF-8 particles have been reported to degrade gradually in water, these studies also suggested a strong concentration dependence where more dilute solution degraded faster, whereas the saturated solutions studied were prepared at far higher concentrations. Furthermore, these nanoZIF-8 methanolic suspensions display visual stability for at least one-month storage, requiring only gentle sonication (∼10 min.)…”
Section: Resultssupporting
confidence: 76%
“…Similarly, VSFSS has emerged as a useful method for a variety of applications since its first observation from particles in liquid by Roke et al in 2003. 17 More recently, VSFSS has been used to determine the mechanism for the stability of “uncharged” nanoemulsions 18 as well as how layer-by-layer deposition of polyelectrolytes can be understood to make nanoemulsions with tunable stability and interfacial properties. 19 Using isotopic dilution in combination with VSFSS, Pullanchery et al found that water has a stronger hydrogen-bonding network near the oil–nanodroplet interface, whereas traditional VSFG in reflection geometry has produced conflicting results.…”
Section: Nonlinear Light Scattering Spectroscopymentioning
confidence: 99%
“…Wang et al 29 and Norouzi et al 40 report on liquid crystals, while Pinẽres-Quinõnes et al 41 characterize emulsions of thermotropic liquid crystals. Hu et al, 42 Neibloom et al, 43 Smith, 44 Richmond, 45 and Langevin 46 all describe recent advances in emulsions.…”
Section: ■ Micelles and Membranesmentioning
confidence: 99%
“…Dr. Phillips’ reflection provides a unique perspective on the lasting influence and legacy of Dr. Greene. Following this personal reflection, we present invited research articles submitted to this VSI to honor Dr. Greene and further recognize the importance of her work in advancing the discipline. We then include selected recent articles published in Langmuir that showcase advances within research areas related to those that Dr. Greene devoted her scientific career to advancing. This collection of articles is divided into four sections that reflect the breadth of topics influenced by Dr. Greene’s accomplishments (Table ).…”
mentioning
confidence: 99%